The Effect Of Branding On Residential Construction With Contoured Land - Rike Nugraha; RA Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
Competition is getting tighter and making consumers more selective in choosing housing on the outskirt of Surabaya. This makes developers have to provide alternative decent housing solutions at affordable prices. Development on contured land in the Menganti sub-district area of gresik regency was chosen because the location is still close to Surabaya. This research was conducted using the phenomenological method, data collection for this research use interview with marketing staff. The research result shoe that there are several criteria that influence consumers choice when buy a home, including paying attention to product quality so that it is resilient to land contours, understanding what consumers want by building infrastructure that is safe against floods and landslide, than building public facilities and park with more attractive architectural design in areas that are considered unprofitable to increase consumer confidence in why it is worth buying in those location. In clonclution, to convince potential consumers, strategy is needed in housing design by applying the design citeria mentioned above in planning safe infrastructure and arranging more attractive public facilities so that the location becomes more profitable. This research aims to analyze the effect of branding on housing on contoured land and in unfavorable plot positions.